2018
DOI: 10.2147/ott.s169823
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of long noncoding RNAs in gastric cancer: a meta-analysis

Abstract: BackgroundIn the last few years, accumulating evidence has indicated that numerous long noncoding RNAs (lncRNAs) are abnormally expressed in gastric cancer (GC) and are associated with the survival of GC patients. This study aimed to conduct a meta-analysis on 19 lncRNAs (AFAP1 antisense RNA 1 [AFAP1-AS1], CDKN2B antisense RNA 1 [ANRIL], cancer susceptibility 15 [CASC15], colon cancer associated transcript 2 [CCAT2], gastric adenocarcinoma associated, positive CD44 regulator, long intergenic noncoding RNA [GAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 110 publications
2
30
0
1
Order By: Relevance
“…Many lncRNAs are currently known to play various roles in gastric carcinogenesis and to provide favorable or unfavorable GC markers, the latter being indicative of disease progression [153]. Similar to protein-coding genes, lncRNAs are classified as oncogenic or tumor suppressors depending on their role in carcinogenesis.…”
Section: Long Noncoding Rnas Involved In the Emt And Regulation Ofmentioning
confidence: 99%
“…Many lncRNAs are currently known to play various roles in gastric carcinogenesis and to provide favorable or unfavorable GC markers, the latter being indicative of disease progression [153]. Similar to protein-coding genes, lncRNAs are classified as oncogenic or tumor suppressors depending on their role in carcinogenesis.…”
Section: Long Noncoding Rnas Involved In the Emt And Regulation Ofmentioning
confidence: 99%
“…7 Moreover, XIST is also known to participate in the progression of several malignant solid tumors, such as gastric cancer, colorectal cancer, retinoblastoma, lung cancer, and liver cancer. [8][9][10][11][12] However, research related to XIST and EOC has been rarely carried out. In this study, we aimed to elucidate the role of XIST in EOC using EOC tissues and cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The present meta-analysis involved 6 studies and revealed that high expression of HOTAIR was significantly associated with poor OS and RFS in CRC patients. Previous studies revealed that HOTAIR overexpression could predict unfavorable outcome in gastric cancer [33,34]. Another meta-analysis showed there was a significant association between high expression of HOTAIR and poor OS in patients with digestive cancers [35,36].…”
Section: Discussionmentioning
confidence: 99%